The potential of native parasitoids for the control of Mexican bean beetles: A genetic and ecological approach - Aebi, Alexandre; Shani, Tal; Hansson, Christer; Contreras-Garduno, Jorge; Mansion, Guilhem; Benrey, Betty (My University, 2008)
Bruchid beetles in the genus Zabrotes are important pests of field and stored beans all around the world and cause enormous economical losses in Mexico and Central America. Native parasitoids have been successfully used to suppress infestations by bruchid beetles in Africa, but few studies have assessed their potential to reduce seed damage in the New World and no successful biological control programs have been implemented, mainly due to the poor knowledge on their biology, systematics and ecology in this region. In this study, we used molecular tools to describe a new complex of three parasitoid species of bruchid beetles in the genus Horismenus, and investigated the level of gene flow and presence of ecotypes in this complex. We also examined the specific association between species of Horismenus and two sibling species of Zabrotes beetles, in order to evaluate their potential as biological control agents. Microsatellite data support the previous morphological description of three species, H. butcheri, H. missouriensis and H. depressus, but suggest some gene flow between H. missouriensis and H. depressus. Host-plant is shown to be the most important factor determining the ecological distribution of the two Zabrotes species, whereas altitude explains most of the distribution of the three Horismenus species. These results complement our understanding of this tritrophic system, providing a solid base for a potential biological control program using native parasitoids.
Keywords: Horismenus; Zabrotes; Ecological distribution; Cryptic species; Wild and cultivated beans; Molecular differentiation; Biological control